Equipment for removing moisture when manipulating piece food products. Issue 1 (1st July 2022) - Avtsinov, I A; Gavrilov, A N; Kudryashov, V S; Sukhanova, N V; Alekseev, M V; Emelyanov, A E
Abstract: The work presents the scientific basis for the recognition of small specific parts and finished products on a thin gas layer. The proposed principle is based on the use of the interlayer as a carrier and recognizing the main element of the pneumatic system. The purpose of the work is to substantiate the possibility of increasing the production of high-quality piece food production through the introduction of modern automated devices. Together with the design features of the working surfaces of the devices, the creation of universal pneumatic equipment is ensured. The developed equipment is able to successfully solve the problems of moisture removal, sorting, rejection, orientation of the subject of production. The description of the recognition principle is given. The synthesis of elements of the pneumatic system of the type "pneumatic chamber-working surface of the device-thin gas layer-product" showed that they are interconnected. At the stage of synthesis of elements of the pneumatic system and their structural classification, it was possible to unite the characteristic specifics of the described pieces of food industry with the design features of the devices and the operations implemented on them. The presented device schemes have versatility, multifunctionality, ability to manipulate specific pieces, when switching from one standard size of parts to another.